Obtaining new potato cultivars with late blight resistance and adapted to climate change using participatory varietal selection - Zúñiga López, Luz Noemí; Gastelo Benavides, Manuel Antonio; Bastos Zuñiga, Carolina; Reyes Espinoza, Jhercy Pepe; Alania, Edson; Ninalaya Cerrón, Evelin Natali (David Publishing Company, 2020)
The potato crop in Peru is the main income and food source for the smallholder of the highland grower of the Peruvian Andes. For urban population, it represents one of the main components of the food basket and for commercial intermediaries. It is the main brokerage product considering its volume and value. To facilitate the adoption and diffusion of new potato cultivars after its release, adequate methodologies are necessary to apply during the process of evaluation and selection. One of these methodologies is called participatory varietal selection (PVS). The objective of this study was to identify new potato cultivars and/or genotypes with resistance or tolerance to adverse effects of climate change applying PVS, in order to obtain new varieties with acceptable economic yields. In this way potato growers of the Peruvian highland Andes should benefit through the improvement of their economic status, food security and overall life quality. During 2016-2017, three potato clones (CIP393079.4, CIP387096.2 and CIP396034.268) and two commercial varieties (Unica, Canchan) were evaluated at eight Peruvian locations in three regions (Huánuco, Junín and Huancavelica). Data were analyzed using a randomized complete block design, with three replications. Main criteria for selection were late blight resistance, abundant foliage, drought tolerance, yield and uniform and healthy tubers. In all three regions the three best clones selected were CIP396034.268, CIP393079.4 and CIP387096.2, ranking in first, second and third place, respectively. Men and women selected the same clones, but in a different order. Commercial cultivars ranked 4th and 5th. However, local growers selected Canchan, CIP387096.2 and CIP393079.4 based on appearance, texture and taste tests. The last two clones (CIP387096.2 and CIP393079.4) should be considered for a future release.